(untitled) (Journal of Universal Science Research, 2023)
It is known that education is the process of conveying information of certain social importance to the younger generation. In a preschool educational institution, it is carried out in the classroom, on walks, in games, in communication with parents, etc. One of the most ancient types of human activity - child education has undergone significant changes during its centuries-old history of development, from a daily process to a complex of scientifically based systematic interaction based on the results of creative and creative activity. It is necessary to learn to manage the pedagogical process in a preschool educational institution under the conditions of introducing pedagogical technologies in the process. These processes were also studied in the article.